Effect of Environmental Performance and Company Size on Financial Performance : Empirical Study of Consumer Goods Sub-Sector Companies Listed on the Indonesia Stock Exchange for the Period 2018-2022 - Al Ayyubi, Muhammad Wafaa; Murti, Galuh Tresna; Aminah, Wiwin; Octari Dinata, Ruri (CV. Publikasi Indonesia, 2024)
This research aims to analyze the influence of environmental performance and company size on financial performance in consumer goods sub-sector companies listed on the IDX for 2018-2022. The research sample consisted of 24 companies with a total of 120 observations. The analysis method uses panel data regression. The findings of the study show that partially environmental performance has a significant positive influence on financial performance, while the size of the company does not have a significant effect. Simultaneously, environmental performance and company size significantly influence financial performance with the ability to explain variations in financial performance by 7%. The study concluded that companies with good environmental performance tended to have better financial performance, while company size was not the main factor affecting financial performance. This study advises management to pay attention to environmental factors in financial performance policies and investors to consider environmental performance in investment decisions.